ATP-binding casette transporter expression in acute myeloid leukemia: association with in vitro cytotoxicity and prognostic markers. (February 2017) - Varatharajan, Savitha; Abraham, Ajay; Karathedath, Sreeja; Ganesan, Sukanya; Lakshmi, Kavitha M; Arthur, Nancy; Srivastava, Vivi M; George, Biju; Srivastava, Alok; Mathews, Vikram; Balasubramanian, Poonkuzhali
Introduction: Drug resistance and relapse are considered to be the major reasons for treatment failure in acute myeloid leukemia (AML). There is limited data on the role of ABC transporter expression on in vitro sensitivity to cytarabine (Ara-C) and daunorubicin (Dnr) in primary AML cells.Patients & methods: RNA expression levels of 12 ABC transporters were analyzed by real-time quantitative PCR in 233 de novo adult acute myeloid leukemia patients. Based on cytarabine or Dnr IC50, the samples were categorized as sensitive, intermediate and resistant. Role of candidate ABC transporter RNA expression on in vitro cytotoxicity, treatment outcome post therapy as well as the influence of various prognostic markers on ABC transporter expression were analyzed.Results: Expression of ABCC3 and ABCB6 were significantly higher in Dnr-resistant samples when compared with Dnr-sensitive samples. Increased ABCC1 expression was associated with poor disease-free survival in this cohort of patients.Conclusion: This comprehensive analysis suggests ABCC1, ABCC3, ABCB6 and ABCA5 as probable targets which can be modulated for improving chemotherapeutic responses.